On early metallurgy and textile-production technologies in the southern Levant: a response to Langgut et al. (2016). (5th June 2017) - Ben-Yosef, Erez; Shamir, Orit; Levy, Janet
Abstract : In a recent article published in this journal, Langgut et al. (2016 : 973) proposed five Late Chalcolithic ( c . 4300–4000 BC) wooden shafts to be "the earliest Near Eastern wooden spinning implements". Here we discuss these unique finds in light of their cultural and technological contexts, and suggest an alternative interpretation according to which these wooden shafts, one with a lead macehead lodged on its upper end, were components of the cultic practices of the southern Levantine Ghassulian culture.